2012
DOI: 10.1242/jeb.070540
|View full text |Cite
|
Sign up to set email alerts
|

A stingless bee can use visual odometry to estimate both height and distance

Abstract: SUMMARYBees move and forage within three dimensions and rely heavily on vision for navigation. The use of vision-based odometry has been studied extensively in horizontal distance measurement, but not vertical distance measurement. The honey bee Apis mellifera and the stingless bee Melipona seminigra measure distance visually using optic flow-movement of images as they pass across the retina. The honey bees gauge height using image motion in the ventral visual field. The stingless bees forage at different trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In tunnel experiments, this tendency is obvious as the 'centering response': bees fly in the middle of the tunnel with symmetric optic flow, but close to one of the walls if it provides no optic flow cues [64,68]. Tunnel experiments also indicated that the stingless bee Melipona panamanica uses optic flow to gauge distance as well as the height of food sources [94]. The nocturnal sweat bee, Megalopta genalis, also uses optic flow in experimental tunnels [95].…”
Section: Flight Ranges and Flight Controlmentioning
confidence: 99%
“…In tunnel experiments, this tendency is obvious as the 'centering response': bees fly in the middle of the tunnel with symmetric optic flow, but close to one of the walls if it provides no optic flow cues [64,68]. Tunnel experiments also indicated that the stingless bee Melipona panamanica uses optic flow to gauge distance as well as the height of food sources [94]. The nocturnal sweat bee, Megalopta genalis, also uses optic flow in experimental tunnels [95].…”
Section: Flight Ranges and Flight Controlmentioning
confidence: 99%
“…Indeed, 3D-moving species acquire spatial information in the vertical plane with a similar or higher accuracy than information in the horizontal plane, whereas surface-bound species are less accurate in the vertical space (Dacke and Srinivasan, 2007;Eckles et al, 2012;Flores-Abreu et al, 2014;Holbrook and Burt de Perera, 2013;Hurly et al, 2010). However, locomotory style does not predict the relative importance of horizontal and vertical information to an animal: vertical information is preferred in fish (both benthic and non-benthic organisms) but not in hummingbirds, two equally 3D-moving species.…”
Section: Introductionmentioning
confidence: 99%
“…Learning vertical spatial information has been demonstrated in bees (Dacke and Srinivasan, 2007;Eckles et al, 2012), but the relative weight of vertical versus horizontal information has not yet been examined in any invertebrate species. Similarly, investigations on how vertical and horizontal information are stored in an internal representation of space (as integrated or separate information) are lacking in invertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…Animals able to move freely in the three dimensions (e.g., fish, bats, bees, birds) encode the vertical information with either equal or higher accuracy than the horizontal information and seem to prefer vertical to horizontal information, while animals constrained to a surface (e.g., rats) do the opposite (Hurly et al, 2010; Holbrook and Burt de Perera, 2013; Davis et al, 2014; Flores-Abreu et al, 2014; but see Ulanovsky, 2011; Savelli and Knierim, 2013; Yartsev and Ulanovsky, 2013; Scatà et al, 2016). However, species of bees that differ in their use of vertical space also differ in the accuracy with which they learn height and in their ability to communicate this information (Nieh et al, 2003; Dacke and Srinivasan, 2007; Eckles et al, 2012). In addition, the performance of a number of species of birds in solving a detour task exclusively on the ground seems to be correlated with the extent to which they move vertically.…”
Section: Introductionmentioning
confidence: 99%